Genome-Wide Scans for Ghanaian Plasmodium falciparum Genes Under Selection From Local and Chinese Host Populations - Shi, Shan-Mei; Shi, Tian-Qi; Chen, Shen-Bo; Cui, Yan-Bing; Kassegne, Kokouvi; Okpeku, Moses; Chen, Jun-Hu; Shen, Hai-Mo (Frontiers in Cellular and Infection Microbiology, 2021)
Initial malarial infection mostly causes symptomatic illness in humans. Infection that is not fatal induces complete protection from severe illness and death, and thus complete protection from severe illness or death is granted with sufficient exposure. However, malaria parasite immunity necessitates constant exposure. Therefore, it is important to evaluate lowered immunity and recurrent susceptibility to symptomatic disease in lower transmission areas. We aimed to investigate selection pressure based on transmission levels, antimalarial drug use, and environmental factors. We whole genome sequenced (WGS) P. falciparum clinical samples from Chinese hosts working in Ghana and compared the results with the WGS data of isolates from native Ghanaians downloaded from pf3k. The P. falciparum samples were generally clustered according to their geographic origin, and Chinese imported samples showed a clear African origin with a slightly different distribution from the native Ghanaian samples. Moreover, samples collected from two host populations showed evidence of differences in the intensity of selection. Compared with native Ghanaian samples, the China-imported isolates exhibited a higher proportion of monoclonal infections, and many genes associated with RBC invasion and immune evasion were found to be under less selection pressure. There was no significant difference in the selection of drug-resistance genes due to a similar artemisinin-based combination therapy medication profile. Local selection of malarial parasites is considered to be a result of differences in the host immunity or disparity in the transmission opportunities of the host. In China, most P. falciparum infections were imported from Africa, and under these circumstances, distinct local selective pressures may be caused by varying acquired immunity and transmission intensity. This study revealed the impact of host switching on the immune system, and it may provide a better understanding of the mechanisms that enable clinical immunity to malaria.